High Prevalence of Sexually Transmitted Infections, and High-Risk Sexual Behaviors Among Indigenous Adolescents of the Comarca Ngäbe-Buglé, Panama. Issue 12 (December 2019) - Gabster, Amanda; Pascale, Juan Miguel; Cislaghi, Beniamino; Francis, Suzanna C.; Weiss, Helen A.; Martinez, Alexander; Ortiz, Alma; Herrera, Mellissa; Herrera, Genarino; Gantes, Cesar; Quiel, Yaremis; Ríos, Adán; et al.
Abstract : Background: There is scant information on sexually transmitted infection (STI) prevalence and risk factors among Latin American indigenous populations. We investigated STI prevalence and risk factors among adolescents of the Comarca Ngäbe-Buglé indigenous region of Panama. Methods: A population-based cross-sectional study was conducted among school-going adolescents aged 14 to 19 years. Eligible consenting participants self-completed a questionnaire and provided blood and urine samples. Female participants provided additional self-administered genital swabs. Seroprevalences of human immunodeficiency virus (HIV), syphilis, hepatitis B (HBsAg, anti-HBc), and herpes simplex virus type 2 (HSV-2) were determined in all participants; genital Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) by PCR among participants who reported sexual experience or were seropositive for HIV/syphilis/HSV2/HBsAg; high-risk human papillomavirus (HPV) by qualitative DNA assay and bacterial vaginosis (BV) by Gram-stain among female participants. Risk factors were identified by estimating adjusted odds ratios (AOR) using random-effects logistic regression. Results: We enrolled 700 participants (median age, 17 years [female participants]; 18 years [male participants]) from 20 schools. Sexual experience was reported by 536 participants (76.6%). The HIV/STI prevalences among females and males were: HIV 0.4% and 1.0%, high-titer active syphilis 1.3% and 6.6%, HSV-2 16.1% and 16.1%, HBsAg 1.3% and 1.4%, anti-HBc 3.2% and 1.4%, NG 1.8% and 1.7%, CT 17.5% and 10.7%; among females: BV 42.9% and HPV 33.2%. CT was independently associated with being female (AOR, 2.02; 95% confidence interval [CI], 1.20–3.41); high-titer active syphilis with being male (AOR, 4.51; 95% CI, 1.17–17.40). Bacterial vaginosis was associated with sexual behavior (≥3 lifetime sex partners: AOR, 3.81; 95% CI, 1.29–11.26), HPV with sexual experience (AOR, 4.05; 95% CI, 1.62–10.09). Conclusions: School-going indigenous adolescents in rural Panama have substantial STI burden. Targeted STI screening is required. Abstract : (WC = 28 of 30): The burden of sexually transmitted infection in Comarca Ngäbe-Buglé high school adolescents is similar or higher than that in urban Panama. There is an urgent need to implement targeted screening and other interventions.Supplemental digital content is available in the text.